Climate change and technology adoption with a large informal sector - Miguel Mascarúa; Ricardo Montañez-Enríquez (Latin American Journal of Central Banking)
What are the aggregate consequences of policies that target adopting more efficient technologies in an economy with a large informal sector? Using a heterogeneous agents model with endogenous occupation choice between workers and formal and informal entrepreneurs and calibrated to Mexico, we found that in economies with a large informal sector, a decrease in the overall tax rate increases by more the adoption of advanced technologies than in economies with a low informal sector. Furthermore, the burden on government revenues is lower in a highly informal economy. In addition, we find that such policies are more efficient than those that target adopting more advanced technologies because they tackle two distortionary problems: the informality rate and the low adoption of advanced technologies. Such policies become relevant, as we estimate that climate change can reduce aggregate production by up to 6.6% in the long-run.